2007
DOI: 10.1099/vir.0.82363-0
|View full text |Cite
|
Sign up to set email alerts
|

Mobility analysis of an NS5A–GFP fusion protein in cells actively replicating hepatitis C virus subgenomic RNA

Abstract: We have introduced GFP and photoactivatable GFP into the NS5A coding region of a hepatitis C virus (HCV) subgenomic replicon that gives efficient transient replication. NS5A-GFP, expressed by the replicon, could be detected in cytoplasmic fluorescent foci as early as 4 h after RNA was introduced into cells. The fluorescent foci are likely to be sites where RNA synthesis could occur, although their production was not dependent on prior replication. Photobleaching studies demonstrated that the fluorescent protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(65 citation statements)
references
References 32 publications
4
60
1
Order By: Relevance
“…Previous FRAP studies performed with components of the HCV replication complex NS4B and NS5A showed that the internal architecture of the membranous web is relatively static, with limited exchange of viral nonstructural proteins between neighboring factories (17,18,54). In the present study, for the first time, we monitored viral RNA dynamics within perinuclear regions of virus replication.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Previous FRAP studies performed with components of the HCV replication complex NS4B and NS5A showed that the internal architecture of the membranous web is relatively static, with limited exchange of viral nonstructural proteins between neighboring factories (17,18,54). In the present study, for the first time, we monitored viral RNA dynamics within perinuclear regions of virus replication.…”
Section: Discussionmentioning
confidence: 90%
“…In order to provide a global picture of the spatiotemporal organization of the RCs, it is therefore important to integrate high-resolution imaging approaches with innovative techniques that allow exploring in real time the dynamic interplay between viruses and their hosts. Engineered subgenomic replicons expressing fluorescently tagged nonstructural proteins (16)(17)(18) have been exploited to investigate the distribution and dynamics of HCV replicase proteins. However, the only available tool to explore flaviviral RNA trafficking has been reported for TBEV (19).…”
mentioning
confidence: 99%
“…Corresponding constructs (SGR-Luc-JFH1 wt/+1 and SGR-Luc-JFH1 wt/21 ) were also constructed for wt SGR-Luc-JFH1. Luciferase activity measured at 4 h after electroporation of RNA into cells, corresponding to a period before the onset of replication and indicative of translation from input RNA (Jones et al, 2007), gave enzyme levels for SGR-Luc-JFH1 poly(A)/+1 and SGR-Luc-JFH1 poly(A)/21 that were 23 and 9.7% of those obtained for SGR-Luc-JFH1 poly(A) (Fig. 5a).…”
Section: Ts Occurs At the Adenine Cluster In Vitromentioning
confidence: 90%
“…CMPD (7) exhibits selective inhibition of PI4KIIIa (IC 50 PI4KIIIa: 7 nM, PI4KIIIb: 1.8 µM), whereas CMPD (3) exhibits a similar selectivity to PIK93 (IC 50 PI4KIIIa: 7.3 µM, PI4KIIIb: 15 nM). As a positive control for inhibition of PI4KIIIa we utilized Huh7.5 cells transiently expressing an HCV subgenomic replicon (SGR-Luc-GFP-JFH1), derived from the JFH-1 infectious clone and containing an insertion of GFP into domain III of NS5A (Jones et al, 2007). This allowed HCV genome replication to be assayed using the IncuCyte system, as described for FMDV above.…”
Section: Resultsmentioning
confidence: 99%
“…Replicons have also been used to study the replication of a number of other viruses. Here, we have also used hepatitis C virus (HCV) sub-genomic replicons pSGR-Luc-GFP-JFH-1 (Jones et al, 2007) and SGR-feo-JFH-1 (Wyles et al, 2009), together with a Coxsackievirus B3 (CVB3) sub-genomic replicon, pRib-Fluc-CB3/T7 (Lanke et al, 2009). …”
Section: Introductionmentioning
confidence: 99%